MODERASI SEBAGAI IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS PANCASILA DI PERGURUAN TINGGI UMUM - Rika Riyanti (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study discusses values and moderation thinking patterns among students which are part of the implementation of Pancasila-based character education in a university environment. The data supporting the call to prayer are all literature data from various sources, especially scientific publications, books, academics, and online database websites—Then, based on the results of the study and discussion, we can conclude that the mindset and values of student life are according to the available evidence. have a high moderating value as part of the character education they find in universities. Thus the results of this study and it is hoped that it can help further research.